Contributing Factors to the Forest Fire from the Community Land Use Surrounding Huay Hout Protection Forest Area, Nan District, Luang Prabang Province, Lao PDR - CHANTHAMALAY, Anoun; KEOHAVONG, Bounmy; DONSAVANH, Beun; PHETDONMO, Phaivanh (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
The study of the factors that influence the occurrence of forest fires from the use of agricultural land and forests of the communities living adjacent to the protected forest area of the ​​Huay hut, Water supply in Nan district, Luang Prabang Province, a case study of 3 villages namely: Phon Hin Village, Paphem Village and Keomani Village, with the aim of proving the factors that lead to forest fires from the activities of agricultural and forestry land use data collection is using an interview form that contains both qualitative and quantitative data. This study used a mixed method (Mixed Research Method) which determined the sample population group with the method of Yamane (1973) with a total of 187 houses of the communities of the three villages and random Purposive Sampling to represent the entire population, was used to analyze the relationship between the factors that affect forest fires with the Enter method of Multi-Linear Regression Analysis with statistical significance p-value ≤0.05. The results of the study found that the people living in the study area who are the head of the family or the representative of the family are mostly male. There are 168 people, covering 89.8 percent. The age is 41-50 years, covering 44.4 percent. The marital status is covering 90.4 percent. The occupation is mostly farmers. There are 166 people, covering 88.8. 7 percent, the majority of the Lao ethnic group accounted for 39.6 percent and most of them do not control the fire, accounting for 91.7 percent. In this, it was found that there are 3 factors that lead to forest fires from the use of agricultural land and forests: 1 is the number of family members that affect the occurrence of forest fires from the use of agricultural land and there are 2 factors that are the status of individuals and occupation has an influence that causes forest fires from the activity of going into the forest to find food sources. These factors are statistically significant at p-value ≤0.05. The results of this study help support government agencies in managing and reducing greenhouse gas emissions from land use.